Video Media Assisted Example Non Example Model on Mathematics Learning Outcomes - Suciani, Desak; Rati, Ni Wayan; Sudatha, I Gde Wawan (Universitas Pendidikan Ganesha, 2020)
The average grade of learning outcomes in class V is low. That is because students' fear of learning and the teacher is not optimal in creating a pleasant atmosphere. This study aims to understand mathematics learning outcomes between students who are taught with example non example learning models assisted with video media and students who are taught discovery learning models assisted with video media in the mathematics subjects of class V. This study includes quasi-experimental uses non-equivalent post designs test only control group design with a population of class V students totaling 128 students. Sampling using a random sampling technique, with a total of 43 students. Mathematics learning outcome data is collected by a test method that is multiple choice objective tests. Mathematical learning outcomes data were analyzed using polled variance t-test. Based on the t-test obtained t count = 7.78> t table = 2.021 at a significance level of 5% (a= 0.05) with db = n1 + n2 - 2 = 43 - 2 = 41 then H0 is rejected. The results of the study prove that the example non example learning model assisted by video media influences on mathematics learning outcomes. The results of this study can be used as a theoretical basis or further learning guidelines to improve learning outcomes, especially mathematics.